2017
DOI: 10.15171/ajmb.2017.03
|View full text |Cite
|
Sign up to set email alerts
|

Renoprotective Effects of Trigonella foenum and Cinnamon on Type 2 Diabetic Rats

Abstract: Background: Herbal medicine is used in all parts of the world mainly for prevention and treatment of various disorders due to better cultural suitability, lower cost and less side effects. Objectives: The aim of this study was to determine the hypoglycemic and kidney-protective effects of the aqueous extract of Trigonella foenum and Cinnamon on diabetic rats. Methods: In this experimental study, rats were randomly divided into 6 groups as follows: Group 1: control group in which animals received chow diet, g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Zarei et al studying on an animal model of diabetes have shown that the aerial parts extract of Salvia hydrangeacan, reduces the blood fat and increases insulin level (31). Also renoprotective effects of fenugreek and cinnamon have been shown on an animal model of type 2 diabetes (32). However, most of these studies did not determine the related mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Zarei et al studying on an animal model of diabetes have shown that the aerial parts extract of Salvia hydrangeacan, reduces the blood fat and increases insulin level (31). Also renoprotective effects of fenugreek and cinnamon have been shown on an animal model of type 2 diabetes (32). However, most of these studies did not determine the related mechanisms.…”
Section: Discussionmentioning
confidence: 99%